Water Carrying Capacity Approach in Spatial Planning: Case Study at Malang Area - Arief Riyadi; Arief Rachmansyah; Bagyo Yanuwiadi (Indonesian Journal of Environment and Sustainable Development, 2018)
The Law of the Republic of Indonesia Number 32 of 2009 and 26 of 2007 affirms that need environmental carrying capacity in preparation of regional spatial plans. The Great Malang bypassed 12 sub-watershed which is 4 of them pass 3 regency / city directly. Therefore, it needs an integrated spatial arrangement between the three regions. The purpose of this research is to formulate study of water carrying capacity (WCC) and recommendation for input in spatial planning in Malang area. The results of the water carrying capacity study show that Metro and the Bango Sub-watershed is very worrying because its critical condition has been exceeded before 2015. While the Amprong and Manten sub-waters are still safe until 2030.Key word: Amprong, Bango, Manten, Metro, Sub-watershed, Water carrying capacity